Technology and the Church: A Theological and Interpretive Approach from the Christian Perspective - Mandla L. Khumalo (ASTEEC, 2025)
The church has been greatly transformed by technology. Many churches have embraced the usage of technology in their ministerial and theological practice. This study examines how these changes are challenging or enhancing current theological practices. This is addressed based on three proposed questions which are; What are the perceptions on the usage of technology by the church? What are the benefits of digitalization to the church? What are the challenges or implications posed by technology to the church? This qualitative study utilizes a theological and interpretive framework in trying to undestand the relationship between technology and religion through the Christian perspective. Data was collected from 12 participants from the Christian faith of which 4 (33%) were pastors and 8 (67%) were disciples. The participants were between the ages of 18-52 in range. Out of the 12 participants, 5 were females and 7 were males. Semi-structured interviews were carried out following snowballing sampling method. The results revealed that technology has positively impacted the church, bringing in new beneficial strategies in spreading the gospel to the world. While technology has been helpful, it has also resulted in unforseen challenges the church has to deal with which include cyber related crime. There is a need to strike a balance to ensure that modern technology does not dillute the original message of the gospel.